Wartime Wisdom: Unveiling Library Resilience in Uzbekistan - Safarova Zilola Safarovna (Universitas Muhammadiyah Sidoarjo, 2024)
This study provides a historical overview of the role of libraries in Uzbekistan during the Second World War, a period marked by extensive martial law. Prior research primarily focuses on military and economic impacts of the war, leaving a knowledge gap regarding cultural and informational services in conflict zones. This research aims to elucidate how libraries adapted to wartime conditions and continued to serve the public despite severe restrictions and resource shortages. Utilizing archival documents and contemporaneous reports, this study reveals that libraries not only managed to maintain operations but also played a pivotal role in sustaining community morale and cultural continuity. The findings indicate that despite significant challenges, libraries demonstrated remarkable resilience and resourcefulness. These insights contribute to a broader understanding of the critical role of information institutions in crisis settings, offering implications for current library science practices and policy formulation in similar contexts. Highlights: Resourcefulness: Libraries maintained operations despite severe resource shortages. Cultural Continuity: They preserved cultural identity and boosted morale. Library Science Implications: Insights from wartime adaptability inform modern crisis management and policy in library science. Keywords: Wartime Libraries, Cultural Resilience, World War II, Information Services, Great Patriotic War